Expression of Hypoxia-Inducible Factor-1α and Myoglobin in Rat Heart as Adaptive Response to Intermittent Hypobaric Hypoxia Exposure - Margaretha Herawati; . Wardaya; Wawan Mulyawan; Fanny Septiani Farhan; Frans Ferdinal; Sri Widia A. Jusman; Mohamad Sadikin (HAYATI Journal of Biosciences, 2017)
The aim of this study was to investigate the influence of intermittent hypobaric hypoxia on the expression hypoxia adaptation proteins, namely hypoxia inducibla factor-1a (HIF-1a) and myoglobin (Mb). Twenty five male Sprague-Dawley rats were exposed to intermittent hypobaric hypoxia in a hypobaric chamber in Indonesian Air Force Institute of Aviation Medicine, for 49.5 minutes at various low pressure, 1 week interval for 4 times (day 1, 8, 15 and 22). HIF-1α and Mb protein were measured with ELISA. mRNA expression of Mb was measured with one step real time RT-PCR. HIF-1α protein levels increased after induction of hypobaric hypoxia and continues to decrease after induction of intermittent hypobaric hypoxia 3 times (ANOVA, p = 0.0437). mRNA expression and protein of Mb increased after induction of hypobaric hypoxia and continues to decrease after induction of intermittent hypobaric hypoxia 3 times (ANOVA, p = 0.0283; 0.0170), and both are strongly correlated (Pearson, r = 0.6307). The heart of rats adapted to intermittent hypoxia conditions by upregulation the expression of HIF-1a and myoglobin and then both return to normal level.